Ultrasound-guided Musculoskeletal Interventions for the Most Common Hip and Pelvis Conditions: A Step-by-Step Approach - Allen, Georgina; Obradov, Marina; Chianca, Vito; Messina, Carmelo; Sconfienza, Luca Maria (Seminars in Musculoskeletal Radiology, 2019)
Pain around the hip and pelvis is a very common condition. Pain may be generated within the joint space (i.e. the hip joint itself, the sacroiliac joints or the pubic symphysis) or from surrounding myotendinous, bursal, or nerve structures. Over the years, percutaneous musculoskeletal procedures have become increasingly popular to diagnose and treat painful conditions around the hip and the pelvis. Most intra- and extra-articular procedures are performed under ultrasound guidance. This article reviews the most common diagnostic and therapeutic procedures that can be performed around the hip and the pelvis under ultrasound guidance.
Keywords: interventional radiology; ultrasound; musculoskeletal system; injection; tendinopathy